KONJUNGSI SEBAGAI PERTALIAN MAKNA ANTARKALIMAT DALAM RUBRIK FUN SCIENCE REPUBLIKA - Sauzan Az Zahra (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2018)
The purpose of study is to describe the use of the conjunction as a relation between the meaning of the sentence in the rubric of Fun Science Republika on January–April 2017 edition. The research method used is descriptive-qualitative. The results showed that the conjunction as a relation between the meaning of the sentence in the rubric of Fun Science Republika on January–April 2017 edition can maintain the integrity of the discourse, namely the cohesion and coherence. Cohesive and coherence of these sections is determined by one of the markers of the relationship, i.e., conjunctions are used as markers of relationship and connection to the meaning of the information revealed that one sentence with the other sentence. The information related to each other and support the existence of harmony to the topic on each speech. The use of the conjunction as a relation between the meaning of the sentence obtained a number of 58 markers of 58 pairs of speech. The use of the mark in relation to the meaning of the ten categories, i.e. the relation of meaning the sums obtained as much as 7% or 4 markers, perturutan 22% or 13 markers, resistance 21% or 12 marker 3% or more, 2 markers, as the result of a 9% or 5 bookmarks, time 17% or 6 markers, terms of 3% or 2 markers, 3% or 5 way marker, uses 2% or 1 bookmark, and explanation of the 7% or 4 markers. The conjunction ‘sequence’ is more widely used as a marker of relationship information between sentences with a total of 22% since the information sequence usually is manifested not only in one sentence, but it needs a few sentences to express the relationship. Thus, the necessary conjunction antarkalimat to link the information so that it supports the main topic. The results of this research as a guide to the development planning implementation study on KD 3.6 and 4.6 class VII junior high school along with the development of teaching materials based on 2013 Revision Curriculum at 2016. Keywords: conjunction, connection between sentence meaning, Republika’s Fun Science rubric Abstrak Tujuan penelitian ini yaitu mendeskripsikan penggunaan konjungsi sebagai pertalian makna antarkalimat pada rubrik Fun Science Republika edisi Januari–April 2017. Metode penelitian yang digunakan, yakni deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa konjungsi sebagai pertalian makna antarkalimat pada rubrik Fun Science Republika edisi Januari–April 2017 dapat mempertahankan keutuhan wacananya, yakni kohesi dan koherensi, dimana informasi kalimat yang satu dengan lainnya bertalian dan mendukung adanya keserasian terhadap topik pada masing-masing ujaran. Penggunaan konjungsi sebagai pertalian makna antarkalimat diperoleh sejumlah 58 penanda dari 58 pasang ujaran. Penggunaan tersebut menandai pertalian makna pada sepuluh kategori, yakni pertalian makna penjumlahan diperoleh sebanyak 7% atau 4 penanda, perturutan 22% atau 13 penanda, perlawanan 21% atau 12 penanda, lebih 3% atau 2 penanda, sebab akibat 9% atau 5 penanda, waktu 17% atau 6 penanda, syarat 3% atau 2 penanda, cara 3% atau 5 penanda, kegunaan 2% atau 1 penanda, dan penjelasan 7% atau 4 penanda. Konjungsi ‘perturutan’ lebih banyak digunakan sebagai penanda hubungan informasi antarkalimat dengan jumlah 22% karena informasi perturutan biasanya diwujudkan tidak dalam satu kalimat saja, namun memerlukan beberapa kalimat untuk menyatakan hubungan tersebut. Dengan demikian, diperlukan konjungsi antarkalimat untuk menghubungkan informasi-informasi tersebut sehingga mendukung topik utama. Hasil penelitian ini dijadikan sebagai panduan pengembangan perencanaan pelaksaan pembelajaran pada KD 3.6 dan 4.6 SMP kelas VII beserta pengembangan materi ajarnya dengan berdasarkan Kurikulum 2013 Tahun 2016. Kata kunci: konjungsi, pertalian makna antarkalimat, rubrik Fun Science Republika